Correlation Between Heart Rate and Left Ventricular Ejection Fraction in Peripartum Cardiomyopathy Patients at RSUP Dr. M. Djamil Padang - Sinai, Nadiva Kezia; Hamdani, Rita; Putra, Andani Eka; Elfi, Eka Fithra; Silvia, Nelmi; Sriyanti, Roza (Fakultas Kedokteran, Universitas Andalas, 2025)
Abstract Background: Peripartum cardiomyopathy (PPCM) is one of the highest preventable causes of death in pregnant women after delivery. Left ventricular ejection fraction (LVEF) describes the degree of damage to myocardial systolic function. Heart rate frequency might be used as one of the prognosis indicators of peripartum cardiomyopathy. Objective: This study aimed to determine the correlation between heart rate frequency at diagnosis and LVEF at diagnosis and after 6 months in patients with PPCM at Dr. M. Djamil Padang Hospital for the period 2017-2021. Methods: This is an observational retrospective analytic study. Samples came from secondary data obtained through the medical records of patients with PPCM at Dr. M. Djamil Padang Hospital for the period 2017-2021, collected using the total sampling technique, 17 samples met the inclusion criteria. Data analysis was performed using simple logistic regression method. Results: The results shows the median age of the patients was 32 years. The average body mass index was 26.32 kg/m2, with hypertension in pregnancy (58.8%), with multiparity (52.9%), delivery by cesarean section (88.2%), diagnosis made postpartum (70.6%), therapy with ACEi/ARB, beta blocker, spirinolactone (100%); LVEF category 20 – 35% (52.9%), delta LVEF more than 10% after 6 months (70.59%). There was no statistically significant relationship between heart rate frequency at diagnosis and LVEF at diagnosis (p > 0.1). There was a statistically significant association between heart rate frequency of 111 - 120 beats per minute at diagnosis and LVEF after 6 months (p < 0.1). Conclusion: There was no association between heart rate frequency and LVEF at diagnosis. There is an association between heart rate frequency of 111 - 120 beats per minute at diagnosis and LVEF after 6 months.